2016
DOI: 10.1039/c5ce02131f
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation behavior of perovskite and anosovite crystals from high Ti-bearing blast furnace slag with small amount of B2O3

Abstract: In the present study, the influence of small additions of B 2 O 3 on the precipitation behavior of perovskite and anosovite from high Ti-bearing blast furnace (Ti-BF) slag was studied at temperature range of 1430-1150 °C, and B 2 O 3 concentration range from 0 to 1.5%. Electron probe X-ray microanalysis (EPMA) was used to determine crystal assemblages of the slags quenched from high temperatures and the compositions of the crystals. X-Ray Diffraction (XRD) was applied to verify mineralogical species of each so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In their work, Å sbrink and Magné li found that high-temperature Ti 3 O 5 was unstable at room temperature; however, it could be stabilized at room temperature through the addition of Fe. Studies concerning anosovite are limited, with the majority of the published literature focusing on separation of anosovite from Ti-bearing slag (Ren et al, 2016;. The carbothermal reduction of TiO 2 to Ti 3 O 5 has also been well documented (Maitre & Lefort, 1999;Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In their work, Å sbrink and Magné li found that high-temperature Ti 3 O 5 was unstable at room temperature; however, it could be stabilized at room temperature through the addition of Fe. Studies concerning anosovite are limited, with the majority of the published literature focusing on separation of anosovite from Ti-bearing slag (Ren et al, 2016;. The carbothermal reduction of TiO 2 to Ti 3 O 5 has also been well documented (Maitre & Lefort, 1999;Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can The structural information of slags could be used to explain the change of properties. Ren et al, 8) investigated the effect of B 2 O 3 on precipitation behavior of perovskite and anosovite crystals, showed that the increasing B 2 O 3 content in the present slags suppress the precipitation of perovskite and promote the formation of anosovite crystal. Zhang et al, 40) also found that the perovskite was suppressed by B 2 O 3 addition in Ti-bearing blast furnace slag.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 99%
“…[3][4][5] The accumulation of titanium slag not only wastes valuable titanium resources but also occupies a large amount of land and seriously pollutes the environment. Since the titanium components in blast furnace slag are mainly dispersed in the mineral phase, such as perovskite, carbon (nitrogen) titanium, and a small amount of spinel and diopside, [6][7][8] this makes it considerably difficult to extract Ti from blast furnace slag. Presently, the utilization rate of titanium in Ti-bearing blast furnace slag is low.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows the XRD pattern of the slag. A broad diffraction peak around 30˝was identified to be CaO-SiO 2 -Al 2 O 3 -TiO 2 glass structure [47], and there was no anatase TiO 2 diffraction peak. Thus, the BFS needs to be treated for getting anatase TiO 2 used as the support of SCR catalyst [17,19].…”
Section: Slag Treatment and Catalyst Preparationmentioning
confidence: 99%
“…Thus, the BFS needs to be treated for getting anatase TiO 2 used as the support of SCR catalyst [17,19]. CaO-SiO2-Al2O3-TiO2 glass structure [47], and there was no anatase TiO2 diffraction peak. Thus, the BFS needs to be treated for getting anatase TiO2 used as the support of SCR catalyst [17,19].…”
Section: Slag Treatment and Catalyst Preparationmentioning
confidence: 99%